Constructing Orange Economy to Sustaining Local Communities in Bali, Indonesia - A. A. Gede Agung Parameswara (Warmadewa Economic Development Journal (WEDJ), 2023)
The sustainability of local communities whose economic and social well-being depends on nature, culture and place-based knowledge is threatened when transfers of ideas, investments and resources occur at the global level in the era of globalization. When global trends have an impact on local populations, traditional ways of managing community resource development may be outdated. Therefore, to support the sustainability of local communities in Bali where culture is at the core of sustainable development, we propose a conceptual framework through a multi-disciplinary approach to guide researchers and policies in these interconnected cultural, economic and social fields. This article reveals three dynamic components; the place identity with local wisdom as a character in which the Balinese concept of the balance and harmony of life between beliefs, nature, and people, known as Tri Hita Karana as the basis, orange economy as an opportunity for economic activities based on a culture that is constructed, and culturally sustainable development and policies that should support the components.